PENERAPAN DATA MINING UNTUK PEMETAAN KINERJA AKADEMIK MAHASISWA DENGAN METODE K-MEANS - G, Katrina Flomina; Rosman, Edwar; Nasution, Muhammad Ibrahim; Febrina, Yerri Kurnia; Hasibuan, Rajimar Suhal (Smart Education, 2025)
Abstract: Implementation of the K-Means clustering algorithm in this study aims to group students based on academic performance in the D3 Teknik Komputer PSDKU Solok Selatan. Clustering is performed based on course grades over 3 semesters, GPA from semester 1 to 3, and student attendance. Data was taken from 27 students who have completed their studies over 3 semesters with a dataset of 29 attributes that will be used in this research. 1 attribute as an identity, 27 attributes underwent a normalization process using MIN-Max Scaler. The clustering process using the Elbow Method and Silhouette Score obtained an optimal cluster k=3, where cluster 0 consists of 10 students, cluster 1 has 8 students, and cluster 2 has 9 students. Cluster 1 shows students with very good academic performance, cluster 2 with diverse academic performance, and cluster 0 with low or poor performance. Principal Component Analysis (PCA) analysis shows good clustering results without overlap. Keyword: Data mining, K-Means clustering, Elbow Method, Silhouette Score, Academic Performance Abstrak: Implementasi algoritma K-Means clustering di penelitian ini bertujuan mengelompokkan mahasiswa berdasarkan kinerja akademik pada Program Studi D3 Teknik Komputer PSDKU Solok Selatan. Clustering dilakukan berdasarkan nilai matakuliah selama 3 semester, IP semester 1 sampai 3 dan absensi kehadiran mahasiswa. Data diambil dari 27 mahasiswa yang telah menyelesaikan perkuliahan selama 3 semester dengan 29 atribut datashet yang akan digunakan pada penelitian ini. 1 atribut sebagai identitas, 27 atribut dilakukan proses normalisasi menggunakan MIN-Max Scaler. Proses clustering dengan Metode Elbow dan Silhouette Score mendapatkan klaster optimal k=3, dimana klaster 0 terdiri dari 10 mahasiswa, klaster 1 terdapat 8 mahasiswa dan klaster 2 terdapat 9 mahasiswa. Klaster 1 menunjukkan mahasiswa dengan kinerja akademik yang sangat baik, klaster 2 dengan kinerja akademik yang beragam dan klaster 0 dengan kinerja yang rendah atau kurang. Analisis Principal Component Analysis (PCA)memnampilkan hasil klastering yang baik tanpa tumpang tindih. Kata kunci: Data mining, K-Means clustering, Elbow Method, Silhoutte Score, Kinerja Akademik